Aplikasi Manajemen Tagihan Berbasis Mobile Dengan Menggunakan Metode Waterfall (Studi Kasus Pada PT.Wiratama Cemerlang) - Master Siregar; Arvin Maulana Hutama (Jurnal Inovasi Informatika, 2021)
At PT. Wiratama Cemerlang, Finance and Collector Department are two parts of the company whose work is related to one another. Where the Finance Department will record and provide a list of jobs for the Collector Department. And the Collector Department will do the work provided by the Finance Department. However, in the process, this work sequence is still using offline method and also has not used technology that can be a place to facilitate information between the two Departments. “Manajemen Tagihan” is a mobile-based job recording application that was built using the Waterfall method for the Finance and Collector Department of PT. Wiratama Cemerlang. This application is useful for both Department because there are two Menu’s that can help both Department dong their work. In this application the Finance Department can record and spread the list of jobs and view reports of job status through jobs reports. And the Collector Department can take the jobs and update the status of job immediately after doing the work so that Finance Department can find out the status of the work being done by the Collector Department